2004
DOI: 10.1038/ng1410
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletions in the human H19 DMR result in loss of IGF2 imprinting and Beckwith-Wiedemann syndrome

Abstract: The overgrowth-and tumor-associated Beckwith-Wiedemann syndrome results from dysregulation of imprinted genes on chromosome 11p15.5. Here we show that inherited microdeletions in the H19 differentially methylated region (DMR) that abolish two CTCF target sites cause this disease. Maternal transmission of the deletions results in hypermethylation of the H19 DMR, biallelic IGF2 expression, H19 silencing and Beckwith-Wiedemann syndrome, indicative of loss of function of the IGF2-H19 imprinting control element.A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
217
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(228 citation statements)
references
References 16 publications
6
217
0
5
Order By: Relevance
“…The following molecular anomalies were identified: 190 IC2-LoM (184 epigenetic anomalies, 5 already published cases with familial IC2 duplications 21 and 1 IC2 deletion), 87 UPD carriers, 31 IC1-GoM (21 already published cases 22,23 including one IC1 duplication, one translocation, 11 familial microdeletions [24][25][26] ), 10 CDKN1C variants (all unrelated cases, 9 maternally inherited). None of the patients tested was positive for genome-wide UPD.…”
Section: Resultsmentioning
confidence: 99%
“…The following molecular anomalies were identified: 190 IC2-LoM (184 epigenetic anomalies, 5 already published cases with familial IC2 duplications 21 and 1 IC2 deletion), 87 UPD carriers, 31 IC1-GoM (21 already published cases 22,23 including one IC1 duplication, one translocation, 11 familial microdeletions [24][25][26] ), 10 CDKN1C variants (all unrelated cases, 9 maternally inherited). None of the patients tested was positive for genome-wide UPD.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, maternally transmitted microdeletion of two CTCF sites in the ICR results in biallelic IGF2 expression and H19 silencing in BeckwithWiedemann syndrome (33). Using nuclear transfer, we previously showed that aberrant IGF2 imprinting in human tumor cells was repaired by the imprinting machinery in the normal fibroblast cytoplasm, leading to monoallelic expression of IGF2 in the reconstructed tumor cybrids or hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are rare micro-deletions at the human H19 ICR that lead to loss of IGF2 imprinting and, hence, BWS. (50,51) One of these small deletions comprised only two of the six CTCF-binding sites at this ICR. Nevertheless, this, somehow, induced hypermethylation along the entire ICR upon maternal transmission, leading to biallelic IGF2 expression and loss of H19 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this, somehow, induced hypermethylation along the entire ICR upon maternal transmission, leading to biallelic IGF2 expression and loss of H19 expression. (50) One possible hypothesis to explain this broad effect is that key elements in the ICR, including the CTCF sites, determine the chromatin and nucleosomal organisation of the entire imprinted domain, thus dictating its behaviour in the germline and during development. (52) Future directions As is often the case with exciting novel data, the discovery that the IGF2-H19 locus is involved in the aetiology of SRS raises many questions.…”
Section: Introductionmentioning
confidence: 99%